Wage inequality in Spain: recent developments - Mario Izquierdo; Aitor Lacuesta (European Central Bank (ECB), 2007)
This paper analyses wage inequality in Spain from 1995 to 2002. Inequality has decreased slightly in this period although the fall has not been constant over the whole distribution. We use non-parametric techniques to distinguish the effect on inequality of changes in the composition of the labour force and changes in relative returns. We focus mainly on three factors that have varied substantially between 1995 and 2002: female participation, educational attainment and changes in the tenure level. On one hand, changes in the composition of the labour force would have increased inequality had the structure of wages not changed in relation to the 1995 level. Changes in education and especially tenure would have been responsible for most of the higher dispersion. On the other, changes in relative returns between 1995 and 2002 are predominant and are responsible for the lower dispersion observed in the latter year. Changes in the returns to education are the main important factor underlying this decrease in inequality.
Keywords: J30; J00; 330; Inequality; labour force composition; wage distribution; Lohnstruktur; Spanien